2014
DOI: 10.2139/ssrn.2377416
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Silence, Insider Selling and Litigation Risk

Abstract: Prior work finds that managers beneficially time their purchases, but not sales, prior to forecasts. Focusing on if (as opposed to when) a forecast is given, we link insider selling to silence in advance of earnings disappointments. This raises the question of whether the absence of incriminating trading drives reductions in litigation risk potentially attributed to warnings. We find that the absence of a warning combined with the presence of selling exacerbates the consequences associated with the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 46 publications
6
57
0
Order By: Relevance
“…Post-earnings announcement trades are measured during the two-week period starting after the release of current quarter's earnings. This choice is to ensure that we capture the earnings-news-related selling, consistent with Billings and Cedergren (2015).…”
Section: Data and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Post-earnings announcement trades are measured during the two-week period starting after the release of current quarter's earnings. This choice is to ensure that we capture the earnings-news-related selling, consistent with Billings and Cedergren (2015).…”
Section: Data and Samplementioning
confidence: 99%
“…(Bettis et al 2000;Huddart et al 2007). Following the classification of trading windows by prior research (Billings and Cedergren 2015), Panel A presents the descriptive statistics for inside purchases by subperiod before earnings announcements, and Panel B presents the corresponding statistics for inside sales after earnings announcements.…”
Section: Data and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have reported that many companies change their disclosure policies after being sued because they gaining a better understanding of the link between disclosure and litigation after going through the litigation process (Kothari et al, 2009;Ball et al, 2012;Billings and Cedergren, 2015). 6 Some researchers have shown a link between the quality of financial reporting, such as earnings management and restatements, and the risk of litigation (Palmrose and Scholz, 2004;Johnson et al, 2007;Cohen et al, 2008;Bardos et al, 2013).…”
Section: Causes Of Patent Lawsuitsmentioning
confidence: 99%
“…10 There are countless examples. Billings and Cedergren (2015) use the presence or absence of earnings forecasts to identify managers who stay silent ahead of earnings disappointments. Yang (2012) uses earnings forecasts to study manager-specific voluntary disclosure style.…”
mentioning
confidence: 99%